1999
DOI: 10.1076/ocii.7.2.61.4023
|View full text |Cite
|
Sign up to set email alerts
|

Tear secretory IgA: evaluation of usefulness as a diagnostic marker in herpetic keratitis

Abstract: In a South Indian study, an 'in-house' enzyme-linked immunosorbent assay (ELISA) was developed to evaluate the potential of herpes simplex virus (HSV)-specific tear secretory IgA (sIgA) in the diagnosis of herpes simplex keratitis (HSK). The presence of HSV-specific tear sIgA was found to be diagnostic in 20.28% of cases. The usefulness of the sIgA ELISA system was evaluated against HSV isolation, which is the 'gold standard' and HSV antigen detection, a more sensitive, commonly employed method. Analysis of HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…15 Our results showed that sIgA was positive in 15 of the 41 stromal keratitis patients (36.59%), and 11 of the 15 positive patients (73.3%) also presented with epithelial lesion. In conformity with previous studies, 9 sIgA was not detected in any of the controls, thereby proving its specificity of the assay. Taking together culture/immunofluorescence assay/ IgG along with sIgA, the diagnostic rate of HSK was significantly higher.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…15 Our results showed that sIgA was positive in 15 of the 41 stromal keratitis patients (36.59%), and 11 of the 15 positive patients (73.3%) also presented with epithelial lesion. In conformity with previous studies, 9 sIgA was not detected in any of the controls, thereby proving its specificity of the assay. Taking together culture/immunofluorescence assay/ IgG along with sIgA, the diagnostic rate of HSK was significantly higher.…”
Section: Discussionsupporting
confidence: 91%
“…Taking together culture/immunofluorescence assay/ IgG along with sIgA, the diagnostic rate of HSK was significantly higher. 9 This suggests that detection of HSV-specific tear sIgA is an indicator of HSK. One factor that may explain the higher positivity in patients with epithelial lesions is the active viral replication within the epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSV-1 infectious disease can be diagnosed specifically by the detection of HSV-1 DNA with the use of the polymerase chain reaction [8], of secretory immunoglobulin A in tear fluid [9], or of HSV-1-specific protein with the use of immunofluorescence analysis [10]. Although these methods are reliable, they have certain disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…Tear samples were used for detecting secretory IgA and/or HSV DNA. We have previously [6, 7, 8]reported the details of the prevalence study based on HSV isolation, antigen detection and tear secretory IgA ELISA. Polymerase chain reaction for HSV DNA detection was standardized using a primer sequence against the HSV thymidine kinase gene and the assay was carried out as per the method of Laycock et al [9].…”
Section: Methodsmentioning
confidence: 99%